Splenic infarction during acute falciparum malaria: A case report - Lu, Youguang; Zhang, Shian; Jiang, Chuanshen (Frontiers in Medicine, 2022)
Splenomegaly is common in malaria, but splenic infarction is a rare complication of malaria. We report a case of a patient with Plasmodium falciparum infection who developed abdominal pain, reappearance of fever, elevated D-dimer during treatment, and abdominal CT confirmed splenic infarction. The abdominal pain was relieved and the fever subsided by analgesic and anticoagulant therapy. Six months later, abdominal CT showed splenic recovery. As a result, splenic infarction should be considered when a patient with malaria developed abdominal pain, reappearance of fever and elevated blood D-dimer during treatment. In the absence of surgical indications, conservative medical treatment is effective.